Effect of Irrigation Regime on Wheat (Triticum aestivum L.) Yield under Shambat Conditions, Sudan - Mohamed, Abdelmoneim Elamin; Mohammed, Mohammed Elhafiz Adam (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted with the objective of determining the effect of application of different irrigation water amounts on the yield of wheat grown on different seedbeds. Three irrigation water regimes namely: 100%, 80% and 60% of crop evapotranspiration (Etc) were used under two types of seedbeds (sowing on the flat and sowing on ridges) over two successive seasons (2003/04–2004/05) at the Demonstration Farm of the Faculty of Agriculture, University of Khartoum, Shambat using a strip-split-plot design with three replications. The control was flat sown and with no-tillage. Data were collected to determine variables pertaining to plant population, plant height, number of tillers, leaf area index (LAI), number of spikelets/plant and grains/spike, 1000-grains weight, harvest index (HI), total grain yield and water use efficiency (WUE). Results obtained revealed that, the watering regime of 60% ETc was statistically inferior in almost all the mentioned parameters, and that the 100% and 80% ETc had similar results in both seasons.